High-Resolution Insights Into the in vitro Developing Blood-Brain Barrier: Novel Morphological Features of Endothelial Nanotube Function - Mentor, Shireen; Fisher, David (Frontiers in Neuroanatomy, 2021)
High-resolution electron microscopy (HREM) imaging of the in vitro blood-brain barrier (BBB), is a promising modality for investigating the dynamic morphological interplay underpinning BBB development. The successful establishment of BBB integrity is grounded in the brain endothelial cells (BEC’s) ability to occlude its paracellular spaces of brain capillaries through the expression of the intercellular tight junction (TJ) proteins. The impermeability of these paracellular spaces are crucial in the regulation of transcellular transport systems to achieve homeostasis of the central nervous system. To-date research describing morphologically, the dynamics by which TJ interaction is orchestrated to successfully construct a specialized barrier remains undescribed. In this study, the application of HREM illuminates the novel, dynamic and highly restrictive BEC paracellular pathway which is founded based on lateral membrane alignment which is the functional imperative for the mechanical juxtapositioning of TJ zones that underpin molecular bonding and sealing of the paracellular space. For the first time, we report on the secretion of a basement membrane in vitro, which allow BECs to orientate themselves into distinct basolateral and apicolateral domains and establish a 3-dimensional BEC construct. We report for the first time, on the expression of nanovesicles bound to the plasma membrane surfaces of the BECs. These membrane-bound vesicles are reported to possess an array of DNA/RNA constituents and chemotaxic properties affecting the formation of nanotubes that span the paracellular space between BECs, facilitating BBB construction, alluding to a functional role in mediating cell-to-cell communication. This study suggests that novel, ultrathin nanotubular (NT) structures are involved in functional roles in bringing into alignment the paracellular space of BECs. Immortalized mouse BECs (b.End3, b.End5) and primary rat cardiac microvascular ECs were used to further validate the in vitro BBB model by profiling variances in peripheral EC monolayer development. These cells presented with an opposite topographical profile: large fenestra and intercellular spaces, devoid of morphological ultrastructures. This comparative study alludes to the role of NT facilitation in TJ-induced hemifusion of apicolateral BEC membranes, as a structural event forming the basis for establishing a polarized BBB.